Implementasi Program Sosialisasi Bimbingan Karir Pada Siswa : Menumbuhkan Cita-Cita dan Motivasi Belajar di Dusun 3 Pasirhalang Desa Langensari - Joko Suprapmanto; M Sulton Abdurrachim; Rahma Audila; Fathiya Kamilatunnuha; Ananta Maulida; Annisa Cikal Destiani; Muhamad Renaldy; Muhamad Rizki Ardiansyah; Denis Ramadia (Fakultas Ekonomi & Bisnis, Universitas Nusa Nipa, 2025)
The Career Guidance Socialization Program in Dusun 3 Pasirhalang, Langensari Village was conducted on Wednesday, February 12, 2025, involving students, teachers, and parents in the learning process. This initiative aims to enhance students' learning motivation and assist them in setting clear educational and career goals. The program provides career socialization and motivational sessions that introduce students to various professions and emphasize the importance of education in achieving a better future.The methods employed in this program include social intervention and Participatory Action Research (PAR), ensuring active participation from students, educators, and parents. Activities include career discussions, motivational speeches, workshops, and interactive sessions designed to increase students' awareness of career opportunities and the necessary steps to achieve their aspirations. Additionally, guidance counseling and religious recitation programs were integrated to strengthen students' character and instill positive values.The results of this initiative indicate a significant increase in student participation, improved awareness of educational and career goals, and enhanced parental involvement in supporting children's education. Many students showed greater enthusiasm in their studies, while parents expressed a better understanding of their role in guiding their children toward academic and professional success. Furthermore, the implementation of follow-up guidance sessions ensured the program's sustainability.Overall, this program has positively impacted the local community by improving educational quality and raising awareness of the importance of learning. By fostering a proactive mindset among students, it is hoped that they will be more motivated to pursue education with a clear vision for their future careers.